2014
DOI: 10.1149/2.0641409jes
|View full text |Cite
|
Sign up to set email alerts
|

In Situ XPS Studies of Electrochemically Positively Polarized Molybdenum Carbide Derived Carbon Double Layer Capacitor Electrode

Abstract: Electrochemical processes at positively polarized Mo 2 C derived carbon (C(Mo 2 C)) electrical double layer capacitor (EDLC) electrode in 1-Ethyl-3-Methylimidazolium tetrafluoroborate ionic liquid at different cell potentials have been studied using in situ synchrotron radiation excited X-ray photoelectron spectroscopy (in-situ XPS) method. Symmetric two-electrode cells were studied using in situ XPS method within very wide cell potential region up to 4.0 V. At cell potentials higher than 2.6 V the cross-over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Comparing our XPS results under vacuum with these previous works, our experiments focused on a relatively smaller potential range (−0.4 to 0.4 V vs. Ag/AgCl QRE). This small range was intentionally used to avoid the potential for faradaic processes leading to IL degradation, as observed in a number of previous vacuum XPS IL studies applied to an electrochemical potential [36–40,43,54,74] . The absence of any evidence of chemical change via XPS (Figure 4) and the absence of faradaic current in the chronoamperometry data (Figures S1 and S2) both support the lack of IL degradation during these experiments.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Comparing our XPS results under vacuum with these previous works, our experiments focused on a relatively smaller potential range (−0.4 to 0.4 V vs. Ag/AgCl QRE). This small range was intentionally used to avoid the potential for faradaic processes leading to IL degradation, as observed in a number of previous vacuum XPS IL studies applied to an electrochemical potential [36–40,43,54,74] . The absence of any evidence of chemical change via XPS (Figure 4) and the absence of faradaic current in the chronoamperometry data (Figures S1 and S2) both support the lack of IL degradation during these experiments.…”
Section: Discussionmentioning
confidence: 62%
“…It has been suggested that performing XPS experiments at IL/vacuum interfaces using soft X‐ray sources allow for probing WE/IL interfaces [35–40,49] . However, this is clearly not the case (see Figure 1b illustration of Au/IL junction) given the probing depth of XPS is on the order of a few nm for a lab‐based soft X‐ray source or soft X‐ray synchrotron source.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without destructive chemical interactions of the IL ion, it is electrochemically stable, but structural changes during cycling are still an important issue and should be carefully considered. To understand the aging or failure mechanism of ILs, electrochemical decomposition of ILs was investigated using in situ techniques (infrared and electrochemical spectroscopy methods and XPS) [45,46]. These studies were performed to understand the EDL structure of ILs, enhancing electrochemical properties by modifying positive or negative ions or adopting pseudoelectrode material.…”
Section: Supercapacitors -Theoretical and Practical Solutionsmentioning
confidence: 99%